STUDI TENTANG RUMAH TANGGA NELAYAN DI KENAGARIAN DUO KOTO DANAU MANINJAU KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Mayuris, Sutria; Juita, Erna; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aims to find out about fishing in meeting household food needs (food), clothing (clothing), board (housing), education and health. The method used in this study is the descriptive research method, research subjects are household heads who were fishermen Nagari Duo Koto Kecamatan Tanjung Raya Agam. Nagari Koto Duo consists of Â 5 oblong, where there are 54 families of fishermen, sampling technique is the total sampling, sample respondents taken as a whole is 100% as much as 54 KK fishermen. Data collection techniques used research questionnaires. Descriptive data analysis techniques in the form of a percentage formula then measured using a Likert scale to see the perception of the respondents on each variable. The results of the five variables showed household needs of fishermen viewed from 1) Meeting the needs of food (food) fishing households have been providing rice as a staple food (100%) it is in excellent condition. 2) Meeting the needs of clothing (apparel) fishermen household availability of purchased clothing are met when the average widths 2 sets and have 1 type of jewelry but the money spent on the average 500,000-Rp. 1000 (59, 25%) were moderate. 3) Meeting the needs of the board (housing) fishing households have toilet facilities, the status of their own house and have an average of 3 rooms, a large kitchen, but mostly kind of home are wood and boards (37, 03%) classified as poor. 4) Meeting the educational needs of households on average fisherman does not graduate junior high (37, 30%) classified as poor. 5) Meeting the health needs have been doing at home MCK activity (95, 59%) as very good and if ill household fishermen went to the clinic for treatment because the nearest health facility is a clinic.